2015
DOI: 10.1021/acs.molpharmaceut.5b00261
|View full text |Cite
|
Sign up to set email alerts
|

A 1H NMR Study of Host/Guest Supramolecular Complexes of a Curcumin Analogue with β-Cyclodextrin and a β-Cyclodextrin-Conjugated Gemini Surfactant

Abstract: Host systems based on β-cyclodextrin (βCD) were employed as pharmaceutical carriers to encapsulate a poorly soluble drug, curcumin analogue (NC 2067), in order to increase its water solubility. βCD was chemically conjugated with an amphiphilic gemini surfactant with the ability to self-assemble and to form nanoscale supramolecular structures. The conjugated molecule, βCDgemini surfactant (βCDg), was shown to be a promising drug delivery agent. In this report, its physicochemical properties were assessed in aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
(89 reference statements)
2
17
0
Order By: Relevance
“…We propose that at [2:1] 18:1βCDg/Mel molar ratio, two 18:1βCDg molecules encapsulate one melphalan molecule forming stable inclusion complexes leading to the higher solubilizing effect. This result is in support of the previous model proposed by our group …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We propose that at [2:1] 18:1βCDg/Mel molar ratio, two 18:1βCDg molecules encapsulate one melphalan molecule forming stable inclusion complexes leading to the higher solubilizing effect. This result is in support of the previous model proposed by our group …”
Section: Resultssupporting
confidence: 93%
“…This property of β‐CD has been employed widely in the pharmaceutical industry to increase the aqueous solubility of hydrophobic moieties with several β‐CD‐based formulations available on the market, such as VFEND ® (voriconazole, an azole antifungal agent) and NEXTERONE ® (amiodarone, an antiarrhythmic medication) among others, and hundred in clinical trials . Previously, our group reported that the βCD‐modified gemini surfactant (12 β CDgemini) is capable of forming guest/host complexes with a hydrophobic anticancer molecule …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase could be due to the fact that Mel is associated with the hydrophobic cavity of the CDgemini, 22 thus protecting it from protein binding in the cell culture milieu 33 and making it more available for cellular uptake. Alternatively, the nanoparticles could carry several molecules and be released, intracellularly, from the endocytosed nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio was selected based on the previous studies of the encapsulation of poorly soluble compounds in CDgemini. [20][21][22] The solvents were removed by speed vacuum, and the nanoparticles were re-suspended either in water or in a 0.5% methylcellulose (Medisca, Montreal, QC, Canada) gel.…”
Section: Nanoparticle Formulationmentioning
confidence: 99%